Asymptomatic secondary abdominal pregnancy diagnosed 12 years after tubectomy - Bulusu, Ratna; Biradar, Kalavathi D.; V., Vijayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Abdominal pregnancy is a rare obstetric complication with high maternal mortality. Advanced abdominal pregnancy is rare and accounts for 1 in 25,000 pregnancies. 32 years’ lady, P2L2, last child birth and interval tubectomy by modified Pomeroy’s method 12 years ago, reported with Amenorrhoea of two months with vague lower abdominal pain since 2 days. Ultrasonography (USG) abdomen and pelvis showed an extrauterine viable pregnancy of 20+ weeks POG with no hemoperitoneum. she travelled 4 hours by road to her hometown, for second opinion and was referred back to our institution. A laparotomy was done; hemoperitoneum of 1.5 litres was noted. The sac with the live foetus inside with placental implantation seen on entire left fallopian tube except the fimbrial end and a small portion of omentum was noted. Left salpingectomy with excision of the sac with the foetus along with partial omentectomy was performed. Patient received two units of PRBC postoperatively.